The cultural politics of contemporary Hollywood film : power, culture and society - Beasley, Chris; Brook, Heather (Manchester University Press, 2019)
Adopting and developing a 'cultural politics' approach, this comprehensive study explores how Hollywood movies generate and reflect political myths about social and personal life that profoundly influence how we understand power relations. Instead of looking at genre, it employs three broad categories of film. 'Security' films present ideas concerning public order and disorder, citizen-state relations and the politics of fear. 'Relationalities' films highlight personal and intimate politics, bringing norms about identities, gender and sexuality into focus. In 'socially critical' films, particular issues and ideas are endowed with more overtly political significance. The book considers these categories as global political technologies implicated in hegemonic and 'soft power' relations whose reach is both deep and broad.